2020
DOI: 10.3171/2020.5.peds20137
|View full text |Cite
|
Sign up to set email alerts
|

Use of fast-sequence spine MRI in pediatric patients

Abstract: OBJECTIVEThe immediate and long-term risk of anesthesia in the pediatric population is controversial. Traditional spine MRI protocols require the patient to remain still during the examination, and in young children this frequently results in the need for sedation administration. The authors’ goal was to develop an abbreviated spine MRI protocol to reduce sedation administration in young patients undergoing spine MRI.METHODSAfter IRB approval, the medical records of all pediatric patients who underwent a fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Included patients in this study had a non-acute headache as the primary neurological manifestation, with a minority of cases presenting nausea/vomiting, dizziness, and syncope. Similarly, previous radiological studies on pediatric patients reported headache [ 15 , 17 , 19 21 , 23 ], vomiting [ 15 , 19 21 ], and syncope [ 19 , 21 ], but also altered mental status [ 15 , 17 , 19 ], seizures [ 15 , 17 , 19 21 ], and pain [ 15 ].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Included patients in this study had a non-acute headache as the primary neurological manifestation, with a minority of cases presenting nausea/vomiting, dizziness, and syncope. Similarly, previous radiological studies on pediatric patients reported headache [ 15 , 17 , 19 21 , 23 ], vomiting [ 15 , 19 21 ], and syncope [ 19 , 21 ], but also altered mental status [ 15 , 17 , 19 ], seizures [ 15 , 17 , 19 21 ], and pain [ 15 ].…”
Section: Discussionsupporting
confidence: 62%
“…Despite the scheduling of clinical CT examinations after two weeks from referral, the clinical question in a majority of patients, as stated in the referral, was “brain tumor?”. Previous studies have investigated the clinical feasibility of fast MRI methods in pediatric patients with hydrocephalus [ 15 , 16 ], acute arterial ischemic stroke [ 17 ], traumatic brain injury [ 18 ], and non-traumatic pediatric emergency [ 19 ], while others have evaluated the diagnostic image quality of fast brain MRI [ 20 22 ] and fast spine MRI [ 23 ]. In accordance with the results from these previous studies, EPIMix performed well in a clinical situation, showing comparable diagnostic performance to CT in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T2 SPACE and HASTE techniques are appealing techniques for abbreviated spine protocols since they can be acquired in the lumbar spine in as little as 3 min for SPACE and much less than a minute for HASTE [26,30]. However, while most reports using T2 SPACE sequences show similar sensitivities and specificities in the detection of degenerative changes in the lumbar spine between rapid and full lumbar spine protocols, it has been previously noted that T2 SPACE sequences may not well evaluate soft tissue and cord lesions [28].…”
Section: Discussionmentioning
confidence: 99%